Quantum-CORMs: quantum dot sensitized CO releasing molecules1. Issue 24 (28th June 2015) - Ruggi, A.; Zobi, F.
<x xml:space="preserve">Abstract</x> Quantum dot sensitized photoactive CORMs show a 2 to 6-fold increase of the photodecomposition rate upon irradiation with visible light.